Comparative Study on the Evaluation of Wind Load on Buildings Using Computational Fluid Dynamics and IS: 875(Part-3) - Ashok, J.; Charles, Shirlin; Umarani, C. (Asian Journal of Engineering and Applied Technology, 2018)
Tall Buildings are highly susceptible to wind induced lateral loads and is required to be designed with greater accuracy. The codal provision IS 875 (part 3) which is usually used, has a limitation that the coefficient of pressure Cpvalues available are, only for 0 and 90 degrees wind incidence angles and for standard cross sections of buildings only. Therefore wind tunnel experiments are carried out to measure wind loads which provide reliable results than the code. This Paper deals with, computational fluid dynamics, an alternative and highly dependable tool to predict the wind related phenomena on buildings. A numerical evaluation of wind pressure is done for the different cases of buildings in IS 875 part-3. Wind load obtained by using IS 875 part-3 are compared with the result obtained from CFD in ANSYS Fluent 15.0 and results are found to be in good agreement .The mean area weighted average values of Coefficient of pressure are also computed for various wind incidence angle.